Evaluasi Kualitas Pelayanan dalam Meningkatkan Kepuasan Pelanggan Menggunakan Metode Servqual (Studi Pada UMKM J-Cello Vermak) - Busyro, Fakhrus Shirooth; Mundari, Siti (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
This study explores the service quality of J-Cello Vermak, a small and medium-sized enterprise (SME) in the garment repair sector, and assesses customer satisfaction using the SERVQUAL method. Established in 2021, the SME faced difficulties in collecting objective data on satisfaction, particularly regarding timeliness, stitching quality, and Responsiveness. A quantitative descriptive method using questionnaires and interviews was used, analyzed using validity and Reliability tests and gap analysis across five SERVQUAL dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. The results indicate generally positive customer satisfaction, with positive gaps across all dimensions. Assurance and Empathy had the highest gaps, reflecting employee trust and Empathy. However, Responsiveness needs improvement due to its lowest gap, indicating a need for faster service. Correlation and regression indicate a weak positive relationship between service quality and satisfaction. Recommendations focus on improving speed, Responsiveness, and ongoing quality management for customer loyalty and competitiveness. These findings are important for the business strategy of SMEs in the garment alteration  service sector. Keywords : Customer satisfaction; Clothing Alterations Service; Service Responsiveness; SERVQUAL; UMKM J-Cello Vermak